Decane hydroconversion on bifunctional Zeogrid and nano-zeolite assembled from aluminosilicate nanoslabs of MFI framework type - Aerts, Alexander; Isacker, Annabel van; Huybrechts, Ward; Kremer, Sebastien P.B; Kirschhock, Christine E.A; Collignon, François; Houthoofd, Kristof; Denayer, Joeri F.M; Baron, Gino V; Marin, Guy B; Jacobs, Pierre A; Martens, Johan A (Applied catalysis. A, General, 2004)
Nanoslabs with MFI zeolite framework topology and having aluminosilicate composition were assembled into nanosize crystals and Zeogrid materials. The nanosize MFI zeolite had a particle size of ca. 200 nm. Micron sized Zeogrid spheres were assembled by precipitating a nanoslab suspension through cetyltrimethylammonium bromide (CTAB) addition and calcination of the precipitate. Zeogrid is a layered structure. Nitrogen adsorption isotherms on Zeogrid revealed the presence of two types of porosity: ultra-microporosity characteristic of MFI type framework and super-microporosity consisting of interlinked parallellopipedic voids occurring in between individual nanoslabs. The incorporation of aluminum in the tetrahedral framework was confirmed with 27 Al MAS NMR. The materials were converted into bifunctional catalysts and evaluated in decane hydroconversion. Surprisingly, the nanosize MFI zeolite and the Zeogrids assembled from MFI type nanoslabs did not show the product selectivity observed with ZSM-5 zeolite prepared using hydrothermal gel method, but rather behaved like large pore zeolites. The unusual behavior is linked with the predominance of wide openings terminating zigzag pores on nanoslab surfaces.